2014
DOI: 10.1111/echo.12635
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Epicardial Fat Thickness to Subclinical Right Ventricular Dysfunction Assessed by Strain and Strain Rate Imaging in Subjects with Metabolic Syndrome: A Two‐Dimensional Speckle Tracking Echocardiography Study

Abstract: Metabolic syndrome is associated with subclinical RV systolic and diastolic dysfunction. In subjects with MetS, increased EFT is independently related to RV systolic and diastolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
(91 reference statements)
2
10
0
Order By: Relevance
“…Ivanovic et al reported that the Tei index as an indicator of global LV function was associated with systemic hypertension, diabetes mellitus, and an increased levels of triglyceride, but not decreased levels of high‐density lipoprotein and higher weight. Gökdeniz et al found that an epicardial adipose tissue thickness was significantly higher in patients with MetS, and that it was correlated with RV myocardial dysfunction. In addition, the MetS was associated with subclinical RV diastolic and systolic dysfunction evaluated by RV free and septal walls strain and RV systolic and early diastolic strain rates.…”
Section: Discussionmentioning
confidence: 98%
“…Ivanovic et al reported that the Tei index as an indicator of global LV function was associated with systemic hypertension, diabetes mellitus, and an increased levels of triglyceride, but not decreased levels of high‐density lipoprotein and higher weight. Gökdeniz et al found that an epicardial adipose tissue thickness was significantly higher in patients with MetS, and that it was correlated with RV myocardial dysfunction. In addition, the MetS was associated with subclinical RV diastolic and systolic dysfunction evaluated by RV free and septal walls strain and RV systolic and early diastolic strain rates.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, there were no differences in RV free wall mechanics indices between subgroups of MetS treated or not for hypertension. Interestingly, Gökdeniz et al [12] did not shown in MetS patients any contributing effect of coexisting hypertension to RV free wall longitudinal strain by speckle tracking imaging. In contrast, systolic blood pressure emerged as an independent contributor to the altered global RV free wall strains reported by Tadic et al [20] in non-diabetic MetS patients.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due in part to the low magnitude of changes observed and a relatively small sample size, although patients acted as their own controls. Accumulation of ectopic fat to the heart is emerging as the key component of myocardial dysfunction in metabolic diseases [12],[47],[52]. Increased epicardial fat, as established in MetS [53] is a local source of pro- and anti-inflammatory cytokines whereas visceral abdominal fat is mainly responsible for the increased systemic inflammation [42],[44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations